As estratégias e a mensuração de resultados em mídias sociais de um grande banco - Gomes, Aguinaldo Tadeu (2023)
This research investigated the measurement of marketing communication strategies in the social media of a large bank. Before, there was the understanding that it was not possible to measure the results of communication actions, as they were intangible actions. Thus, measuring the results of their actions has always been a major challenge for communication managers. But with the emergence of social media and the advancement of digital technologies, this understanding has changed and today it is possible to measure communication actions. In order to carry out this research, it was necessary to study some theoretical aspects of the subject, such as communication management in organizations, measurement in marketing communication, return on investment in communication, social media and also measurement metrics of marketing strategies communication. As a research method, first a narrative bibliographical review was carried out, dealing with the main concepts involved in the project. Afterwards, the strategy of a single case study was chosen in the typical case modality, as it was understood that the company studied, a large bank, expresses an ideal type of the category. The case study was based on documentary research and also through individual interviews with the professionals who work in the team responsible for evaluating the performance of campaigns carried out on social media by the institution's Marketing Board. The result of this dissertation recognizes the importance of measuring marketing communication strategies in social media, understanding that in the face of a competitive and challenging scenario, companies need to make every penny invested in marketing communication actions count. It is necessary to know how to measure the results of communication actions in order to arrive at the best tools and strategies that justify the investments made.